Dokumenty i sud'by . Dokumenty i sud'by . Documents and Destinies . Документы и судьбы - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Examination of archival documents about an informer from Karlsruhe, who sent the information about the activity of a revolutionary circle to the Police Department of St. Petersburg in 1893. Contributors: Mironenko, Sergei (Anchor) Рассмотрение архивных документов, рассказывающих историю доносчика из Карлсруэ, сообщавшему в 1893 году в Департамент полиции Санкт-Петербурга о деятельности революционного кружка. Создатели: Мироненко, Сергей (Ведущий/Ведущая)